(untitled) (Research, Society and Development, 2021)
This research aimed to investigate the perceptions of perinatal care professionals regarding the communication of bad news and deaths in the perinatal context. This is an exploratory descriptive research, with a qualitative and quantitative approach. Twenty-seven perinatal hospital care professionals participated in the study, among these obstetric nurses, nursing technicians, nurses residing in obstetric nursing, obstetric gynecologists. The collection was made through a questionnaire with questions organized through a likert scale and open questions that were submitted to Content Analysis. The data reveal how difficult it is for professionals to experience perinatal loss and deal with the communication of bad news. It is concluded that in the perception of professionals of perinatal care they feel little prepared for the communication of bad news and perinatal deaths.